Media Promotion of Halal Tourism in Vietnam: Opportunities, Challenges and Some Policy Implications - Thi Minh Tam, Vu; Thuy Linh, Phan; Duc Ha, Chu; Van Viet, Ta; Van Truong, Phung (VNU Journal of Science: Policy and Management Studies, 2025)
Ab stract : The article analyzes the opportunities and challenges of communication in promoting Halal tourism in Vietnam through a synthesis of existing literature, comparative policy review, and examination of international best practices. It identifies core barriers and highlights emerging opportunities within the sector. Building on these insights, the article proposes a “5C” Halal Communication Framework that includes: Commitment (integrating Halal objectives into national, regional, and local strategies), Certification (establishing transparent mechanisms for Halal certification and labeling), Content (multilingual, multicultural, and Halal-compliant communication materials), Community (collaboration with Muslim communities and influencers), and Customer Experience (enhancing service and destination experiences). The expected contribution is to strengthen policy and market communication capacities, thereby supporting Vietnam’s positioning as a friendly, safe, and trustworthy Halal-ready destination. Keywords: Halal tourism, communication, Islam.